2018
DOI: 10.5213/inj.1836078.039
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-Sensitive Sensory Nerves Indirectly Modulate Motor Function of the Urinary Bladder

Abstract: PurposeThe urinary bladder (UB) is innervated by both sensory and autonomic nerves. Recent studies have shown that sensory neuropeptides induced contractions in the detrusor muscle. Therefore, in a mouse model, we investigated the presence of interactions between the submucosal sensory nerves and the autonomic nerves that regulate the motor function of the detrusor muscle.MethodsUB samples from male C57BL/6 mice were isolated, cut into strips, and mounted in an organ bath. Dose-response curves to norepinephrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Recent studies have shown similar results in the lower urinary tract. The inhibitory effect of GUA on the noradrenergic innervation was observed in the bladder detrusor in mice [ 36 ] and rats [ 51 ], and in the urinary bladder neck in pigs [ 38 ]. It is believed that decrease in the density of noradrenergic fibers in target tissues caused by the action of GUA is related to its direct sympathomimetic effect leading to the release of NA from stores in the effector organs [ 52 ], which is followed by inhibition of the re-uptake and re-synthesis of NA, leading to its depletion in the noradrenergic varicosities [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown similar results in the lower urinary tract. The inhibitory effect of GUA on the noradrenergic innervation was observed in the bladder detrusor in mice [ 36 ] and rats [ 51 ], and in the urinary bladder neck in pigs [ 38 ]. It is believed that decrease in the density of noradrenergic fibers in target tissues caused by the action of GUA is related to its direct sympathomimetic effect leading to the release of NA from stores in the effector organs [ 52 ], which is followed by inhibition of the re-uptake and re-synthesis of NA, leading to its depletion in the noradrenergic varicosities [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in most species, including humans, α 1 -adrenoceptor stimulation produces weak detrusor contraction, whereas a stronger contraction is observed in the trigone, bladder base and/or in the bladder neck [ 63 ]. On the other hand, it has been observed that activation of α 1 adrenergic receptors in the urothelium in rats [ 64 ], and the treatment of sensory submucosal nerve fibers in mice [ 36 ] with phenylephrine leads to the release of some unknown neurotransmitters from both sources, which in turn facilitate detrusor relaxation, probably by augmentation of noradrenaline release from the sympathetic nerves. Subsequently, noradrenaline stimulates β-adrenoceptors on the detrusor muscle, leading to relaxation of the urinary bladder [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is mediated by capsaicin-sensitive prostate afferents. Chang et al [ 11 ] propose that in mice, phenylephrine activates the α-1A adrenergic receptor of a sensory nerve, and then activates a capsaicin-sensitive sensory nerve, causing it to release an unknown substance that facilitates the release of norepinephrine from adrenergic nerves. Subsequently, norepinephrine stimulates β-adrenergic receptors in the detrusor muscle, which leads to neurogenic relaxation of the bladder.…”
mentioning
confidence: 99%